2018
DOI: 10.1016/j.ophtha.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

A Database Study of Visual Outcomes and Intraoperative Complications of Postvitrectomy Cataract Surgery

Abstract: We found a significant improvement in VA with postvitrectomy cataract surgery. However, compared with eyes without prior PPV, there was a worse mean postoperative vision of 0.2 logMAR units, a higher rate of zonular dialysis and dropped nuclear fragments, and a similar rate of posterior capsule rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
7
38
3
Order By: Relevance
“…D UE TO THE CONTINUOUS ADVANCES IN INSTRUmentation and surgical technique, the indications of pars plana vitrectomy (PPV) have expanded and have become a common surgical procedure for various vitreoretinal disorders, such as retinal detachment, macular hole, macular pucker, proliferative diabetic retinopathy, and vitreous hemorrhage. 1,2 One of the wellknown sequela of vitrectomy is the cataract formation or acceleration, [3][4][5] with up to 80% within 2 years. 2,[6][7][8] Studies have suggested that light toxicity, oxidation of lens proteins, use of intraocular gas or silicone oil, length of surgery, mechanical trauma, and increased postoperative oxygen tension within the eye may be causative factors of cataract after PPV.…”
mentioning
confidence: 99%
“…D UE TO THE CONTINUOUS ADVANCES IN INSTRUmentation and surgical technique, the indications of pars plana vitrectomy (PPV) have expanded and have become a common surgical procedure for various vitreoretinal disorders, such as retinal detachment, macular hole, macular pucker, proliferative diabetic retinopathy, and vitreous hemorrhage. 1,2 One of the wellknown sequela of vitrectomy is the cataract formation or acceleration, [3][4][5] with up to 80% within 2 years. 2,[6][7][8] Studies have suggested that light toxicity, oxidation of lens proteins, use of intraocular gas or silicone oil, length of surgery, mechanical trauma, and increased postoperative oxygen tension within the eye may be causative factors of cataract after PPV.…”
mentioning
confidence: 99%
“…In these patients, anterior chamber fluctuations and deep anterior chamber increased mobility in the posterior lens, and zonular instability can be observed during cataract surgery due to the lack of vitreous support. During a vitrectomy, direct zonules or lens damage may develop, and the reactive effect of tamponade on zonules may cause zonular weakness (14). Any of these conditions may increase the risk of preoperative complications during cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Cataract is the most common complication of pars plana vitrectomy (PPV) used extensively to treat various posterior segment pathologies [1,2]. Phacoemulsification cataract surgery is associated with more complications in an eye after PPV compared with nonvitrectomized eyes [3][4][5][6]. e prevalence of posterior capsule rupture (PCR) in nonvitrectomized eyes is 1.92 to 3.5% [7].…”
Section: Introductionmentioning
confidence: 99%
“…e prevalence of posterior capsule rupture (PCR) in nonvitrectomized eyes is 1.92 to 3.5% [7]. In contrast, the reported rates of PCR in vitrectomized eyes were up to 13.3%, accompanied with a higher rate of zonular dialysis, dropped nuclear fragments, and choroidal exudation [3,4,6,8,9]. e situation is relevant to anatomical changes of a vitrectomized eye that shows reduced vitreous gel support, possibly with defective zonular apparatus, and an impaired or fibrotic lens capsule [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation